P266 IL-4/13 inhibitor dupilumab associated with new onset peripheral axial spondyloarthritis in patients with atopic dermatitis. (20th April 2020) - Hughes, Catherine D; Menon, Bina; Willsmore, Zena; Woolf, Richard; Smith, Catherine; Pink, Andrew; Kirkham, Bruce W
Abstract: Background: Dupilumab is a recombinant human monoclonal antibody that inhibits signalling of interleukin-4 and interleukin-13. It has NICE approval for use in patients with moderate to severe atopic eczema who have failed at least one standard therapy. The main reported side effects in clinical trials were allergic conjunctivitis (1-5%), injection site reactions (8-19%) and herpes viral infections (3-7%). Methods: Here we report symptoms and signs of a new peripheral axial spondyloarthritis/ psoriatic arthritis type presentation in 8 patients within 16 weeks of commencing dupilumab. This has not been described previously in the clinical trials patient population. Results: These patients had a long history of atopy with severe eczema and raised baseline IgE levels of > 12000. A positive response to dupilumab was seen in all patients as evidenced by marked improvements in the Eczema Area and Severity Index (EASI). Musculoskeletal symptom onset began between 2 and 16 weeks after commencement of drug. Patients typically complained of inflammatory type pain in the small joints and entheseal sites. 2/8 patients had inflammatory sounding spinal pain. Early morning stiffness was common. All patients had normal acute phase reactants and one patient had a positive rheumatoid factor. 6/8 patients had radiologically evident enthesitis as seen on MRI or ultrasound (power doppler ultrasound signal-PDUS). 3/8 patients had such severe symptoms that they had to discontinue dupilumab. All patients were commenced on non-steroidal anti inflammatories. One patient was commenced on a low dose JAK inhibitor and exhibited improvement in musculoskeletal symptoms. Conclusion: IL-4 has been shown to suppress delayed type hypersensitivity reactions (DTHRs) in both human and mice studies. It has been demonstrated previously that IL-4 can prevent bone erosion and disease progression in animal models of inflammatory arthritis. Guenova et al (2015) showed that IL-4 can selectively suppress IL-23 transcription and secretion with reduced Th17 function. They suggest that administration of IL-4 may be of therapeutic benefit in Th17 mediated inflammatory conditions. Conversely, dupilumab through the inhibition of IL-4 and IL-13 and possible resultant increased IL-17 and IL-23 levels, has perhaps unmasked a tendency towards development of a peripheral axial SpA phenotype in these patients. Disclosures: C.D. Hughes None. B. Menon None. Z. Willsmore None. R. Woolf None. C. Smith Grants/research support; CS is a PI/CoPI on a number of commercially supported studie (Abbvie, Janssen, Leo, Sanofi). A. Pink None. B.W. Kirkham Consultancies; BK has worked as a consultant for Eli Lilly, Gilead, Janssen and Novartis. Grants/research support; BK has received research support from Eli Lilly and Novartis.